Single-dose azithromycin for child growth in Burkina Faso: a randomized controlled trial - Ali Sié; Boubacar Coulibaly; Clarisse Dah; Mamadou Bountogo; Mamadou Ouattara; Guillaume Compaoré; Jessica M. Brogdon; William W. Godwin; Elodie Lebas; Thuy Doan; Benjamin F. Arnold; Travis C. Porco; et al. (BMC, 2021)
Abstract Background In lower resource settings, previous randomized controlled trials have demonstrated evidence of increased weight gain following antibiotic administration in children with acute illness. We conducted an individually randomized trial to assess whether single dose azithromycin treatment causes weight gain in a general population sample of children in Burkina Faso. Methods Children aged 8 days to 59 months were enrolled in November 2019 and followed through June 2020 in Nouna Town, Burkina Faso. Participants were randomly assigned to a single oral dose of azithromycin (20 mg/kg) or matching placebo. Anthropometric measurements were collected at baseline and 14 days and 6 months after enrollment. The primary anthropometric outcome was weight gain velocity in g/kg/day from baseline to 14 days and 6 months in separate linear regression models. Results Of 450 enrolled children, 230 were randomly assigned to azithromycin and 220 to placebo. Median age was 26 months (IQR 16 to 38 months) and 51% were female. At 14 days, children in the azithromycin arm gained a mean difference of 0.9 g/kg/day (95% CI 0.2 to 1.6 g/kg/day, P = 0.01) more than children in the placebo arm. There was no difference in weight gain velocity in children receiving azithromycin compared to placebo at 6 months (mean difference 0.04 g/kg/day, 95% CI − 0.05 to 0.13 g/kg/day, P = 0.46). There were no significant differences in other anthropometric outcomes. Conclusions Transient increases in weight gain were observed after oral azithromycin treatment, which may provide short-term benefits. Clinical trials registration ClinicalTrials.gov NCT03676751 . Registered 19/09/2018.